Development of a Nursing Standards for Drug Emergency Patients - อาภาบุษยพันธุ์, รุจิรา; นิลบรรพ์, สำเนา; ชัยพิชิตพันธ์, นันทา; จีนประชา, ญาดา; ยี่ภู่, จรุณรักษ์ (Journal of The Royal Thai Army Nurses, 2019)
This study was a research and development aiming to study and develop a nursing standard for drug emergency patients. The research was divided into three phase; (1) surveying and investigating the background of the problem, (2) developing the nursing standard for drug emergency patients (3) assessing the result of the guideline. The research sample comprised of three groups. The first sample group was 20 people of medical and nurse administrators, registered nurses and patient’s relatives. The second group of the sample was 20 specialists, and the third group consisted of 75 patients, 32 relatives and 38 registered nurses. The research instruments comprised of a semi - structured interview question, a feedback questionnaire for the nursing standard, a patient’s severity classification form, a satisfied questionnaire for the relative, a knowledge measurement form, a performance assessing form and a satisfied questionnaire for the qualified nurse. The analysis methods were a content analysis, a descriptive statistic and a paired sample t-test. The result indicated that; (1) the classification and referral systems, the standard guideline and knowledge enhancement for the related staffs should be developed, (2) five nursing standard for drug emergency patients has been launched, and (3) most of the patient was the critical condition and urgent patients, and the nurses can follow well the guideline. The score of the post-test was significantly higher than pretest at 0.05. The satisfaction of the relatives and nurses on the guideline was very good level.